Piecewise Analytic Method VS Runge-Kutta Method (Comparative Study) - Abassy, Tamer (International Journal of Applied Mathematical Research, 2020)
Even though Runge-Kutta (RK) method is the most used by scientists and engineers, it is not the most powerful method. In this paper, a comparative study between Piecewise Analytic Method (PAM) and RK methods is achieved. The result of comparative study shows that PAM is more powerful and gives results better than RK Methods. PAM can be considered as a new step in the evolution of solving nonlinear differential equations.